Post-Traumatic Stress Disorder (PTSD) Among Landslide Survivors: a Descriptive Study - Cahyani, Hanif Eka; Warsini, Sri; Raymomdalexas, Carla Marchira (Universitas Airlangga, 2023)
Introduction: Natural disasters present numerous challenges for survivors. One significant outcome is trauma, which can lead to the development of post traumatic stress disorder (PTSD). This study aimed to assess the prevalence of PTSD and identify its predictor factors among survivors of a landslide disaster in the Donorati Village community, Purworejo, Indonesia. Method: This study used a descriptive cross-sectional design with a quantitative approach, focusing on landslide survivors in the Purworejo district. A sample of 100 individuals from Donorati village was selected through cluster and consecutive sampling. Key variables included PTSD, gender, age, education, socio-economic status, marital status, disaster severity, prior exposure, impact of the landslide (house damage, injuries, and fatalities), and evacuation records. Data were collected using a demographic form and The Impact of Event Scale-Revised (IES-R). Bivariate analysis utilized Chi-squared and Fisher’s tests, while multivariate analysis used logistic regression. Results: The prevalence of PTSD among participants was 27%. Bivariate analysis showed significant differences in PTSD levels related to sex (p = 0.02), age (p = 0.009), occupation (p = 0.02), disaster severity (p = 0.008), injured family members (p = 0.018), and evacuation history (p = 0.001). Multivariate analysis highlighted gender and disaster severity as key factors linked to PTSD after the landslide. Conclusions: PTSD levels varied significantly by gender, age, occupation, disaster severity, presence of injured family members, and evacuation history. This finding highlights the urgent need for mental health and psychosocial support services to help disaster survivors cope effectively.